Polyhydroxyalkanoates (PHA) production from fermented thermal-hydrolyzed sludge by PHA-storing denitrifiers integrating PHA accumulation with nitrate removal. (November 2019) - Tu, Weiming; Zhang, Dandan; Wang, Hui; Lin, Ziyu
Graphic abstract: Highlights: Aerobic-feast and anoxic-famine regime was applied for culture selection. Energy input of aeration was reduced by 79% compared with the aerobic regime. PHA yield on VFA of 0.47 gCOD/gCOD and nitrate removal of 98% were achieved. Accumulation of nitrite and nitrous oxide during the process were investigated. Integration of PHA production with wastewater treatment was designed. Abstract: Polyhydroxyalkanoates (PHA) production from fermented thermal-hydrolyzed sludge was conducted by mixed microbial cultures (MMCs) in the study. An MMC enriched in the species Brachymonas_denitrificans (60.18%) was selected under an aerobic feast/famine regime, which is capable of denitrification and accumulating PHA. To take advantage of the PHA-storing denitrifiers, an aerobic-feast/anoxic-famine regime was applied to integrate culture selection with denitrification. The results showed that cultures enriched under the regime exhibited a PHA storage capacity with PHA yield on VFA of 0.47 gCOD/gCOD and well denitrification performance achieving nitrate removal of 98%. Moreover, the aerobic-feast/anoxic-famine regime could originate a comparable maximum PHA content to the complete aerobic feast/famine regime (49.7 wt% versus. 47.1 wt%, respectively), yet reduce aeration energy input by 79% in the culture selection process. Finally, this study investigated the accumulation of nitrite and nitrous oxide during PHA based denitrification and the feasibility of integrating the process with wastewater treatment.